2017
DOI: 10.3389/fphys.2017.00356
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role for LPA3 in Cardiac Hypertrophy Induced by Myocardial Infarction but Not by Isoproterenol

Abstract: Background: We previously reported that lysophosphatidic acid (LPA) promoted cardiomyocyte hypertrophy in vitro via one of its G protein-coupled receptor subtypes, LPA3. In this study, we examined the role of LPA3 in cardiac hypertrophy induced by isoproterenol (ISO) and myocardial infarction.Methods: In vitro, neonatal rat cardiomyocytes (NRCMs) were subjected to LPA3 knocked-down, or pretreated with a β-adrenergic receptor (β-AR) antagonist (propranolol) before LPA/ISO treatment. Cardiomyocyte size and hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Despite recent studies implicating LPA receptor signaling in cardiovascular disease [ 9 13 ] and obesity/diabetes [ 20 , 22 24 , 30 32 ], it remains unclear which of the six so far identified LPA receptors (LPA1-6) are expressed in the heart and cardiomyocytes and whether myocardial LPA receptor expression is regulated by changes in metabolic status. Therefore, we examined LPA receptor mRNA levels in the heart from mice that were fed either chow or HFHS diet for 16 weeks in the fed state and following a 16-h fast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent studies implicating LPA receptor signaling in cardiovascular disease [ 9 13 ] and obesity/diabetes [ 20 , 22 24 , 30 32 ], it remains unclear which of the six so far identified LPA receptors (LPA1-6) are expressed in the heart and cardiomyocytes and whether myocardial LPA receptor expression is regulated by changes in metabolic status. Therefore, we examined LPA receptor mRNA levels in the heart from mice that were fed either chow or HFHS diet for 16 weeks in the fed state and following a 16-h fast.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies also showed that LPA levels increase with myocardial infarction [ 16 , 17 ]. On the other hand, a recent study suggested that LPA1 and LPA3 signaling provide a protective effect against ischemia-reperfusion injury in rats and sequelae from myocardial infarction in mice [ 11 , 13 ]. Bouchareb et al [ 12 ] identified the autotaxin-LPA signaling axis as a major contributor to aortic valve stenosis as it promotes aortic valve inflammation and mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…These data indirectly support the findings in the current study. In addition, LPA3 knockout mice exhibited reduced cardiac hypertrophy compared to wild-type mice post-MI ( Cai et al, 2017 ), indicating that LPA/LPA3 signaling is required for cardiac hypertrophy after MI. In terms of regulation of cardiac hypertrophy, this report supports the mention in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we tested whether the up-regulation of CPA4 in hypertrophic hearts was conserved across species. Cardiac hypertrophy was induced in C57BL/6 mice by subcutaneous treatment of ISO (50 mg/kg/day) for continuous 28 days using a protocol reported previously [22]. ISO treatment induced the decrease in fraction shortening and ejection fraction in mice ( Figure 1D,E).…”
Section: The Expression Of Cpa4 Is Up-regulated In Human and Mouse Hymentioning
confidence: 68%
“…Mice were anesthetized with isoflurane and body temperature maintained on a circulating heated waterpad. The cardiac hypertrophy in mouse was induced by subcutaneously chronic infusion of ISO (Sigma; 50 mg/kg/day) with ALZet minipump 2004 for 28 days, as described in previous work [22]. The animal experiments were performed in the Animal Center of Hebei Medical University.…”
Section: Animal Studymentioning
confidence: 99%